THE EFFECT OF 635 BRAINWRITING TECHNIQUES ON TENTH-GRADE STUDENTS’ WRITING COMPETENCE AT SMAN 3 SINGARAJA - Komang Ayu Karisma Widayani; I Nyoman Adi Jaya Putra; Ni Luh Putu Eka Sulistia Dewi (Universitas Suryakancana, 2026)
This study aims to investigate the effect of the 635 Brainwriting technique on tenth-gradestudents’ writing competence. The researchers used a quasi-experimental design by employing aPost-Test Only Control Group design. The population was taken from all tenth-grade students ofSMA Negeri 3 Singaraja in the academic year 2024/2025. A cluster random sampling techniquewas applied to select the sample. The sample was 72 tenth-grade students, who were divided intoan experimental and a control group. In the experimental group, the students were taught usingthe 635 Brainwriting technique, while in the control group, students were treated using theconventional technique (PPP). The data were analyzed using descriptive and inferential statisticsanalysis. Results of the data analysis showed the mean score of the experimental group was83.67, while the control group was 80.89. For hypothesis testing, a paired sample t-test wasconducted. The result showed a sig. (2-tailed) value of 0.004, which was lower than the standardAlpha level 0.05 (p < 0.05). This proved that the 635 Brainwriting technique produced asignificant influence on the experimental group. Therefore, the 635 Brainwriting technique wasproven to be effective in generating students’ ideas in writing recount text.